RENCANA KESELAMATAN DAN KESEHATAN KERJA (K3) KONTRAK PADA PEMBANGUNAN GEDUNG SEKOLAH DASAR IMMANUEL PONTIANAK - Prayetti, Maulidiah Dwi; Rafie, -; Pratiwi, Riyanny (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
Accident in work can be happened anytime when the construction project has been started, that caseÂ happening because of limitation in safety tools, sightseeing to workers, less experience from workers, bad behavior,still bad to planning, or because of the workers usually handling their works and inattentive about the dangerous that always aim them. Accident thats happening can make physical defect or even death.The purpose of this safety and healthy works in construction field to knowing and understanding with well the meaning of applied safety and healthy works, especially at every construction activity service, doing the good job, following the rules,limitation and steps who signed agree with safety and healthy workers orientation at workplace, can avoiding any accident chance at workplace with prevention and fixing,sightseeing to fulfill the safety and healthy works in order to workers and everyone always in safety and well condition at workplace,so the sources can processing without any obstacle. In this Immanuel School development, planning of safety and healthy works contracts was doing to avoid accident thats normally happened in small or big scale.K3 contracts plan started with analyzing the accident thats already happened,as well as the cause of accidents from 3 main factor is humans factor, kinds of work factor and implemention method, and some nature factors too. Because of results from 3 main factor at beforethe way of avoiding can planed with well, after that continuing with evalution of k3 procedures during of construction process, this evaluation purpose to controlling the k3 procedures suitable with the plan. Kata Kunci : Rencana Keselamatan dan Kesehatan Kerja Kontrak (RK3K)